2017
DOI: 10.1016/j.trc.2016.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of reduced visibility on traffic crash risk using microscopic data and surrogate safety measures

Abstract: Due to the difficulty of obtaining accurate real-time visibility and vehicle based traffic data at the same time, there are only few research studies that addressed the impact of reduced visibility on traffic crash risk. This research was conducted based on a new visibility detection system by mounting visibility sensor arrays combined with adaptive learning modules to provide more accurate visibility detections. The vehicle-based detector, Wavetronix SmartSensor HD, was installed at the same place to collect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 22 publications
(18 reference statements)
0
26
0
Order By: Relevance
“…The site selected is based on an earlier report by Abdel-Aty et al [ 22 ] on I-4 in Polk County, where higher crashes related to adverse weather occurred. More information about the site can be referred to Peng et al [ 23 ]. Each adverse weather monitor system (ADMS) was installed roadside and consists of three sensors at increasing elevations beginning at one foot one inch.…”
Section: Data Collection and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The site selected is based on an earlier report by Abdel-Aty et al [ 22 ] on I-4 in Polk County, where higher crashes related to adverse weather occurred. More information about the site can be referred to Peng et al [ 23 ]. Each adverse weather monitor system (ADMS) was installed roadside and consists of three sensors at increasing elevations beginning at one foot one inch.…”
Section: Data Collection and Methodologymentioning
confidence: 99%
“…As it was pointed out at the end of the conclusion and discuss section, the current conclusions of this paper are mainly based on the data collected on the highway I-4 in Polk County, Florida. Additional description about the data can be referred to Peng et al[ 23 ]. It is meaningful to collect the traffic and weather data from other types of road segments to obtain more comprehensive analysis results on the effect of adverse weather in the future.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Hjelkrem and Ryeng [3] showed that low-visibility weather presented a greater risk for safe car following. Low-visibility weather can also easily lead to erroneous driver manoeuvres such as overreactions, physiological fluctuations, and psychological fluctuations, which can be reflected in driving safety [4]. Yannis et al [5] noted that accident severity increased with a reduction in visibility.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable death rate chiefly imputes secondary crashes than first impacts, shown as accident statistics in recent years. 1,2 Feeling panic-stricken in a collision, human drivers may operate the post-impact vehicle hastily and arbitrarily, particularly for inexperienced drivers. A high risk of consequent crashes can be induced easily which cause injuries and deaths.…”
Section: Introductionmentioning
confidence: 99%
“…Active front steering (AFS) and differential braking controllers were designed for stability enhancement and quick response. 1,5 Since over-actuated drive is capable of control performance improvement and active safety enhancement, it became a primary measure to eliminate yaw moment disturbance in hazardous after-collision cases. 6 Based on tracking the percussion center and tested on an Audi TTS, 5 a combined control framework was developed that a feedforward portion can function better in vehicle stabilization as the tires were approaching to physical adhesion limits.…”
Section: Introductionmentioning
confidence: 99%